EPIDEMIOLOGY OF PANCREATIC CANCER - Muratović, Belma; Nikolić, Aleksandra (HEALTH CARE, 2023)
Pancreatic cancer is the seventh leading cause of cancer-related deaths and the twelfth most common cancer worldwide. Incidence and mortality rates vary from country to country, which is a consequence of exposure to different risk factors, the possibilities of early diagnosis and timely and adequate treatment. It is estimated that by 2040, there will be a further increase in the number of patients (e.g. by 27.4% in Europe) and deaths (e.g. by 28.5% in Europe) caused by pancreatic cancer. According to the National Cancer Institute of the United States of America, the average five-year survival rate for pancreatic cancer is 12%. Modifiable and non-modifiable factors contribute to the occurrence of this tumor. Pancreatic cancer occurs more often in the elderly, men, tobacco and alcohol users, people with diabetes, chronic pancreatitis, physically inactive and obese people, as well as in people with a positive family history of this malignant tumor. It is necessary to work on educating the population about the risk factors for pancreatic cancer, the possibilities of prevention and ways of early diagnosis of this disease.